2018
DOI: 10.2478/jvetres-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Amitraz marker residues in honey from honeybee colonies treated with Apiwarol

Abstract: IntroductionAmitraz is a formamide exhibiting both acaricidal and insecticidal activity and is frequently used by beekeepers to protect honeybee colonies against Varroa destructor mites. The aim of this apiary trial was to evaluate the impact of honeybee colony fumigation with amitraz on the level of contamination of honey stored in combs.Material and MethodsExperimental colonies were fumigated four times every four days with one tablet of Apiwarol per treatment. Honey was sampled from combs of brood chambers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In the present study, to select suitable reference genes, we chose five candidate reference genes including 40S ribosomal protein S5 (RPS5), 40S ribosomal protein S18 (RPS18), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), ADP-ribosylation factor 1 (ARF1), and Rasrelated protein Rab-1A (RAD1a), which have been previously used as reference genes in honey bee studies [28,30,32]. Previous studies showed that honey bee is accidently exposed to various pesticides, and exposure of these pesticides negatively affect honey bee colonies, therefore, we chose seven pesticides (neonicotinoids: acetamiprid and imidacloprid, butanolide: flupyradifurone, organophosphate: fenitrothion, carbamate: carbaryl, formamidine: amitraz, and pyrethroid: bifenthrin) [33][34][35][36][37][38]. In addition, considering that different tissues might involve different detoxification mechanisms [39], we dissected five body parts (head, thorax, gut, fat body, and carcass) from honey bees treated with the seven pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, to select suitable reference genes, we chose five candidate reference genes including 40S ribosomal protein S5 (RPS5), 40S ribosomal protein S18 (RPS18), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), ADP-ribosylation factor 1 (ARF1), and Rasrelated protein Rab-1A (RAD1a), which have been previously used as reference genes in honey bee studies [28,30,32]. Previous studies showed that honey bee is accidently exposed to various pesticides, and exposure of these pesticides negatively affect honey bee colonies, therefore, we chose seven pesticides (neonicotinoids: acetamiprid and imidacloprid, butanolide: flupyradifurone, organophosphate: fenitrothion, carbamate: carbaryl, formamidine: amitraz, and pyrethroid: bifenthrin) [33][34][35][36][37][38]. In addition, considering that different tissues might involve different detoxification mechanisms [39], we dissected five body parts (head, thorax, gut, fat body, and carcass) from honey bees treated with the seven pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental rate decrease and bee survival decrease in individuals treated with amitraz was found by Dai et al (2018). Recent studies by Kiljanek et al (2017), Pohorecka et al (2017Pohorecka et al ( , 2018 indicate a potential problem related to amitraz residues in honey bees and their products, and the relatively low effectiveness of measures performed in colonies with brood could be due to the development of V. destructor resistant strains. The efficacy of amitraz treatments executed in broodless colonies and results of the evaluation varroacidal activity of other veterinary preparations containing amitraz WÄ™grzynowicz et al, 2017) proves the opposite point of view.…”
Section: Discussionmentioning
confidence: 90%
“…These data reflect that the action undertaken by beekeepers towards fighting Varroa mites are insufficient. For more than thirty years treatment based on amitraz (formulation Apiwarol® and Biowar 500®) have been used by most beekeepers (Pohorecka et al, 2014), which seriously risks the contamination of apiculture products (Kiljanek et al, 2017;Pohorecka et al, 2017Pohorecka et al, , 2018 and the possibility to select more resistant strains of V. destructor (Pohorecka & Bober, 2007, 2008Maggi et al, 2010;Kamler et al, 2016). Low field effectiveness of the administered drug are frequently caused by incorrectly performed treatment procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Pohorecka and coworkers [ 32 ] investigated two different methods of amitraz application in hives. The hives were fumigated four times every four days with one tablet of 12.5 mg amitraz or given at the same time, but with indirect smoke generation (tablets of 12.5 mg amitraz were combusted in a Wakont electric fumigator) and introduced to entrances of hives through a nozzle.…”
Section: Discussionmentioning
confidence: 99%